Factors affecting treatment decisions for Class I malocclusions - Eka Erwansyah; Jihad Randika Basra; Rika Damayanyi (Makassar Dental Journal PDGI Makassar, 2020)
Background: Malocclusion is a worldwide dental problem that influences the affected individuals to varying degrees. Many factors contribute to the anomaly in dentition, including hereditary and environmental aspects. Dental caries, pulp and periapical lesions, dental trauma, abnormality of development, and oral habits are most common dental diseases in children that strongly relate to malocclusion. Objective: The objective of this article is to describe the factors affecting treatment decisions for class I malocclusions. Methods: Scientific evidence and clinical cases are taken from literatures to support the clear and detailed informations about treatment decisions for class I malocclusions. Conclusion: In the treatment of Class I malocclusion orthodontics, there are two main information, extraction and treatement without extraction. Consideration for tooth extraction is something that must be done carefully.